2019
DOI: 10.3389/fpls.2019.01026
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Morphological, Physiological, and Biochemical Responses to Light Quality in Barley Leaves and Roots

Abstract: Light quality modulates plant growth, development, physiology, and metabolism through a series of photoreceptors perceiving light signal and related signaling pathways. Although the partial mechanisms of the responses to light quality are well understood, how plants orchestrate these impacts on the levels of above- and below-ground tissues and molecular, physiological, and morphological processes remains unclear. However, the re-allocation of plant resources can substantially adjust plant tolerance to stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 111 publications
5
29
0
2
Order By: Relevance
“…It was shown that the R: FR ratio affects different steps of plant nutrition that are critical for enhanced and sustainable crop production. It can affect root structure (De Simone et al, 2000;Gundel et al, 2014) or root growth (Klem et al, 2019). The establishment of a nitrogen-fixing symbiosis between legumes and rhizobia requires not only sufficient primary metabolites but also the sensing of the R : FR ratio (Suzuki et al, 2011).…”
Section: Fr and Yield Qualitymentioning
confidence: 99%
“…It was shown that the R: FR ratio affects different steps of plant nutrition that are critical for enhanced and sustainable crop production. It can affect root structure (De Simone et al, 2000;Gundel et al, 2014) or root growth (Klem et al, 2019). The establishment of a nitrogen-fixing symbiosis between legumes and rhizobia requires not only sufficient primary metabolites but also the sensing of the R : FR ratio (Suzuki et al, 2011).…”
Section: Fr and Yield Qualitymentioning
confidence: 99%
“…Показатели площади листьев, продолжительность их работы и накопление сухой биомассы определяют продуктивность фотосинтетической деятельности посевов. Площадь листьев является одним из важных показателей, характеризующих фотосинтетическую деятельность растений, и урожай тесно связан именно с размерами площади листьев [14,16,17].…”
Section: растениеводствоunclassified
“…Fluctuating light is ubiquitous within canopy, and all leaves are shaded to some degree during their lifecycle. Shaded light is characterized by low light intensity (decreased PAR), a low red/far-red light ratio and low blue light 23 25 . PAR is a primary driving force for photosynthesis, and different wavelengths of light are considered to be important environmental signals 25 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Shaded light is characterized by low light intensity (decreased PAR), a low red/far-red light ratio and low blue light 23 25 . PAR is a primary driving force for photosynthesis, and different wavelengths of light are considered to be important environmental signals 25 27 . Circadian clock is an internal timing mechanism that allows plants as sessile organisms to synchronize with environmental cues 28 .…”
Section: Introductionmentioning
confidence: 99%